Monetary policy analysis towards inflation and capital market performance - Ahmad Rodoni, (Penerbit Universiti Kebangsaan Malaysia, 2006)
This research is designed to analyze the monetary policy towards inflation and capital market performance during 1998 - 2004 period. The objectives of this research are: first, to analyze the direct influence of interest rate, base money, and exchange rate toward inflation and also to analyze the direct influence of interest rate, base money, and exchange rate toward capital market performance. Second, to analyze the indirect influence of interest rate, base money and exchange rate through inflation toward return market. Path Analysis is used as the research method. The result indicates that there have been some significant effects between interest rate, base money. and exchange rate toward inflation and return market. Indirect influence of interest rate, base money, and exchange rate toward return market through inflation arrives at 4.176%. Overall. the direct and indirect influence of macroeconomics variables toward return market reach 22.941 %.